Trends and critical points of Aspergillus contamination along Ethiopian chili postharvest value chain - Tariku Hunduma Tolera; Anteneh Tesfaye; Melaku Alemu (CABI Agriculture and Bioscience)
Abstract Background Chili is the most commonly grown spice in Ethiopia and is a high-value crop for household consumption and sale both at domestic and export markets. However, an unsafe level of fungal toxins is becoming a problem leading to challenges in exporting. This study assessed trends, possible points of Aspergillus contamination, and contamination risk factors along the Ethiopian chili postharvest value chain (PVC). Methods Chili handling practices, value chain actors, and their respective roles were investigated along the PVC through an exploratory type of research, a participant unstructured observation. A total of 214 individual sample units composed of multiple subsamples consisting of aseptically picked matured red pods (PiPP), dried red pods (DPP), crushed chili (CP), unpacked (UpPPo), and packed chili powder (PaPPo) were randomly collected along the PVC from different major chili growing localities of Ethiopia during 2017/2018 main cropping season. Individual sample units were further homogenized into a fine powder and composited. Aspergillus was analyzed using Aspergillus flavus and parasiticus agar medium. To monitor Aspergillus contamination, trend analysis was done using the mean of count data and biological inference was made in association with stages of operations and postharvest handling practices. Results Aspergillus was detected in 44% of PiPP, all (100%) of DPP, CP, UpPPo, and PaPPo. Counts were in the range of 5.00 × 103 to 2.10 × 105 CFU g−1 up along the PVC with fold changes of 19.6, 30, 42, and 38-fold in DPP, CP, UpPPo, and PaPPo, respectively. Nigri (99%), Flavi (85%), and Circumdati (56%) were the most detected sections with relative densities of 50, 29, and 14%, respectively. Postharvest handling practices such as harvesting, sun-drying, and transporting were generally found poor and unhygienic. Conclusions Counts of Aspergillus showed gradually increasing trends up along the PVC. The poor and unhygienic handling practices probably contributed to the contamination. Harvesting and direct open sun-drying were likely initial and critical points of contamination while wetting and tight stacking likely contributed to aggravated growth and proliferation of aspergilli leading to further consecutive buildup. Intervention at these stages would make a significant difference.